Definition and measurement of reproductive health - Sadana Ritu (The World Health Organization, 2002)
ABSTRACT: An internationally agreed conceptual definition of reproductive health is applied to the development and testing of practical indicators for use in the community. Basic criteria are proposed for an interview-based tool to measure reproductive health - as opposed to morbidity or mortality - adapting methods from the health status measurement field. Proposed domains and indicators linked to the definition of reproductive health adopted at the International Conference on Population and Development (ICPD) should be comparable across and within diverse populations. Two sets of domains that describe reproductive health are recommended for further development and testing, seven domains that focus directly on health and six others that assess related areas of well-being.